STUDI FITOPLANKTON DI DANAU TONDANO PROVINSI SULAWESI UTARA - Manu, Gaspar; Baroleh, Martinus; Kambey, Alex D (Sam Ratulangi University, 2010)
This research was conducted in Tondano Lake North Sulawesi for 3 month from June to August 2007. The research was aimed to identify species abundance of phytoplankton. Phytoplankton were collected by using a 40 μm large plankton net. Results showed that phytoplankton consisted of 32 genera. It also indicated that the highest individual abundance was shown by Fragillaria (2903 individuals), followed by Microspora (2349 individuals), Closterium ( 984 individuals), Zynema (803 individuals), Melosira (770 individuals), and Anabaena (693 individuals) respectively with monthly sampling the highest abundance was on August (4227 individuals), followed by June (3516 individuals), and July (3493 individuals).